Use of indwelling pleural/peritoneal catheter in the management of malignant ascites: a retrospective study of 48 patients. Issue 6 (14th June 2020) - Chan, Ka P.; Badiei, Arash; Tan, Carmen P. S.; Fitzgerald, Deirdre B.; Stanley, Christopher; Fysh, Edward T. H.; Shrestha, Ranjan; Muruganandan, Sanjeevan; Read, Catherine A.; Thomas, Rajesh; Lee, Yun Chor Gary
Abstract: Background: Patients suffering from malignant ascites usually require repeated large volume paracentesis (LVP) for symptomatic relief. This often requires hospital admission and has inherent risks. Aims: To report the first Australian experience of placing tunnelled indwelling peritoneal catheters (IPeC) for management of recurrent malignant ascites. Methods: A retrospective study was conducted of tunnelled IPeC use in patients with symptomatic malignant ascites in four hospitals in Western Australia (from 2010 to 2018). Procedure data, success rate and safety profile were collected from a database. Results: Forty‐eight patients (median age 65 years; female 56%) underwent 51 peritoneal catheter insertion procedures that were performed mostly by pleural specialists. The majority of patients (96%) had prior LVP (median two drainages, interquartile range (IQR) 1–4) before IPeC insertion. The IPeC was inserted successfully under ultrasound guidance in all patients. The median length of hospital stay for IPeC insertion and initial ascites drainage was 2 days (IQR 2–3 days) and most patients (96%) did not require further paracentesis after IPeC placement. The majority (96%) of patients experienced relief from ascites symptoms after catheter insertion. Most IPeC‐related adverse events were self‐limiting, including pain (in 25% cases), transient hypotension after initial fluid drainage (10%), peritoneal fluid leakage (10%), bacterial peritonitis (8%), fluid loculation (2%) and catheter dislodgement (2%). Six (12%) patients had IPeC removed. All patients with bacterial peritonitis responded to antibiotics and one required catheter removal. Conclusions: Use of tunnelled IPeC improves symptoms and can minimise further invasive drainage procedures in patients with symptomatic malignant ascites. Placement of IPeC was associated with a low rate of adverse events, most of which could be managed conservatively.